A real-world study of the efficacy and tolerability of fremanezumab in migraine patients with a median follow-up of 14 months - Shiho Suzuki; Keisuke Suzuki; Yasuo Haruyama; Hiroaki Fujita; Tomohiko Shiina; Saro Kobayashi; Mukuto Shioda; Ryotaro Hida; Koichi Hirata (Neurological Research and Practice)
Abstract Background To evaluate the long-term efficacy and safety of fremanezumab over a 2-year period in a real-world setting. Methods This retrospective, observational, single-center cohort study included 165 patients with episodic migraine (EM) or chronic migraine (CM) who received fremanezumab treatment. The primary endpoint was the change in monthly migraine days (MMDs) from baseline to months 1–24. The secondary endpoints included changes in Migraine Disability Assessment (MIDAS) scores, adverse events, response rates, predictors for responders, and treatment persistence. Results In the entire cohort, the MMD changes from baseline at 3, 6, 12, and 24 months were  − 7.2 ± 4.7,  − 8.1 ± 6.3,  − 8.4 ± 5.1, and  − 9.6 ± 6.0 days, respectively (p < 0.001). After 3, 6, 12, and 24 months, the ≥ 50% response rates were 57.0%, 63.6%, 63.5%, and 69.0%, respectively. The MIDAS score significantly decreased in the total sample and the EM and CM groups. No significant difference in efficacy was found between the monthly and quarterly dosing groups. Adverse events, mainly injection site reactions, occurred in 13.3% of the patients, and 2.4% of the participants discontinued treatment due to side effects. There were different clinical backgrounds between non-responders, and early and ultra-late responders, including psychiatric complications, medication overuse headache, and pulsatile headache. The treatment continuation rates at 12, 18, and 24 months were 73.5%, 65.4%, and 58.0%, respectively, with higher persistence in patients who received quarterly dosing than in those who received monthly dosing (p < 0.001). Conclusion Fremanezumab is effective and well tolerated for long-term migraine prophylaxis.